“Text-Led” or “Idea-Led” Literary Theories Eliminating Marginalization. Undercutting Eurocentric (Culture), Androcentric (Gender), and Heterosexual Supremacy (Sexual Orientation) - Gehlot, Lalit; Alkhalaf, Hailah; Srivastava, Dr. Prerna; Gokhru , Swati; Noval, Sangeetha; Choudhary, Dr Ritu Raj (Journal of Education Culture and Society, 2025)
Aim. This paper aims to find the origin of major literary theories and their domains. Literary theories often bear differences under the three major categories, “Eurocentrism”, “Androcentricism”, and “Heterosexual Supremacy”. Out of which, “Eurocentricism” talks about the Western look at the rest of the world as begging, illogical, unscientific, and strange (cultural sense of other), “Androcentricism” vents out gender marginalization and “Heterosexual Supremacy” excludes homosexuality. Methods. Some major theories are interpreted under the above given three segregations like Structuralism removes all the Western dominance (Eurocentricism) or Gender biases (Androcentricism) shown in the text with lexis, codes, and interspersed digressions, and the Queer theory rejects the “Heterosexual Supremacy”. Special preference is given to theories which are idea-led. Results. This research highlights that in the ‘Text-led’ theories, Structuralism, Post-Structuralism, Russian Formalism and Sigmund Freud’s Psychoanalysis work on the text to find the generalized meaning of the text, and in the ‘Idea-led’ philosophies like Louis Althusser’s Marxism, New Historicism or Cultural Materialism focus on ideas with wider approach of accepting the fact that a literary work is affected by multiple causes and can result in various interpretations of the works. Conclusion. This research tries to prove that marginalization is the genesis of literary theories, as these theories serve as tools to expose overtly the process of marginalization to the world. This research paper also talks about bisexuality’s support by any new theory that has yet to register in the list of literary theories. This research paper proves that all literary theories are developed for some widespread generic reasons in favour of the betterment of our society. Reading this research one can find the real way to apply the literary theories for discourse analysis.